Pengaruh Beban Kerja dan Teknologi Informasi Kerja terhadap Komitmen Organisasi Karyawan pada PT Matahari Department Store Tbk Solo Square - Bunga Anggelina Putri; Agus Suyatno; Taufiq Nur Muftiyanto; Umi Hanifah (Excellent, 2026)
This research investigates employee organizational commitment, workload, and work-related information technology at PT Matahari Department Store Tbk Solo Square. This research is quantitative and causal. The sample was established using the Slovin formula, resulting in 70 respondents chosen from a total of 238 employees via a purposive sampling method. Data were gathered through a 1-5 Likert scale questionnaire and analyzed with SPSS version 27. This research employed validity, reliability, classical assumption evaluations, multiple linear regression analysis, t-tests, and R² values. The findings indicated that both workload and work-related information technology affect organizational commitment at PT Matahari Department Store Tbk Solo Square. This research can assist organizations in balancing workloads fairly and enhancing information technology to boost employee commitment to the organization.